Patterns of alluvial deposition in Andean lake consistent with ENSO trigger. (1st May 2021) - Hagemans, Kimberley; Nooren, Kees; de Haas, Tjalling; Córdova, Mario; Hennekam, Rick; Stekelenburg, Martin C.A.; Rodbell, Donald T.; Middelkoop, Hans; Donders, Timme H.
Abstract: The laminated sediment record from Laguna Pallcacocha, Ecuador, is widely used as a sensitive recorder of past variability in the El Niño-Southern Oscillation. However, limited knowledge of local meteorology, hydrogeomorphic processes, and the lateral variability of the lacustrine stratigraphy have resulted in some ambiguity in proxy interpretation. In this study, we report new high-resolution meteorological data, hydrogeomorphic mapping of the catchment and geochemistry of the lake's sediments. We show that the fine clastic layers are deposited from alluvial activity in the catchment related to intensive rainfall events originating from the Pacific. Frequency analyses of the geochemistry of the sediments indicates that the clastic layers in L. Pallcacocha fall into the characteristic ENSO frequency band and most likely record Eastern Pacific and Coastal Pacific El Niño events. We also illustrate that recent debris flow deposition has resulted in an abrupt avulsion of the main fluvial channels, redirecting sediment input between the lake's two basins and possibly influencing the lithostratigraphy of the sediment package of L. Pallcacocha. Highlights: Clastic sediment layers from L. Pallcacocha are deposits from Pacific rainfall-driven alluvial activity in the catchment. The occurrence of fine clastic layers in the sediments of L. Pallcacocha fall into the characteristic ENSO frequency band. The sediments of L. Pallcacocha most likely record Eastern Pacific and Coastal Pacific El Niño events. Recent debris flow deposition has resulted in an avulsion of the main fluvial channels draining to the lake's two basins. Such a redirection of sediment input possibly influences the lithostratigraphy of the sediment package of L. Pallcacocha.